2022
DOI: 10.1136/bmjopen-2021-050450
|View full text |Cite
|
Sign up to set email alerts
|

Importance of sex and gender factors for COVID-19 infection and hospitalisation: a sex-stratified analysis using machine learning in UK Biobank data

Abstract: ObjectiveTo examine sex and gender roles in COVID-19 test positivity and hospitalisation in sex-stratified predictive models using machine learning.DesignCross-sectional study.SettingUK Biobank prospective cohort.ParticipantsParticipants tested between 16 March 2020 and 18 May 2020 were analysed.Main outcome measuresThe endpoints of the study were COVID-19 test positivity and hospitalisation. Forty-two individuals’ demographics, psychosocial factors and comorbidities were used as likely determinants of outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
2
10
0
1
Order By: Relevance
“…This study shows that the willingness of male residents in Chinese communities to be vaccinated is 1.48 times that of female residents in Chinese communities. The gender difference reflected by this vaccination may be related to the higher mortality rate of COVID-19 in men than in women, which is consistent with previous research results in China and internationally (17)(18)(19); a study (20) has reported that in the COVID-19 pandemic, women generally implement non-drug intervention measures such as wearing masks and washing hands frequently, so it can be summarized that men tend to vaccinate and women tend to use non-drug intervention to prevent COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…This study shows that the willingness of male residents in Chinese communities to be vaccinated is 1.48 times that of female residents in Chinese communities. The gender difference reflected by this vaccination may be related to the higher mortality rate of COVID-19 in men than in women, which is consistent with previous research results in China and internationally (17)(18)(19); a study (20) has reported that in the COVID-19 pandemic, women generally implement non-drug intervention measures such as wearing masks and washing hands frequently, so it can be summarized that men tend to vaccinate and women tend to use non-drug intervention to prevent COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Sakatani et al [ 29 ] utilized a machine-learning approach to estimate human cerebral atrophy on the basis of metabolic status. Shiba et al [ 30 ] identified high risk factors for COVID-19 infection and hospitalization utilizing UK biobank data with machine-learning-based analysis. In addition, there are several previous works applying machine-learning methods for diagnosing NAFLD by utilizing electronic medical records or biochemical variables ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the availability of data it might be worthy to test the effect of gender using a composite measure as was performed by GENESIS-PRAXY Investigators [9,10]. The methodology of constructing the gender score has been validated since the inception in cohorts from retrospective and prospective studies [11][12][13][14][15][16][17][18][19]. Furthermore, international scientists have been supporting the assessment of even one domain or few individual gender-related factors depending on the availability of data [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The applicability of the GENESIS-PRAXY methodology using retrospective cohorts have been tested in other contexts [11,12] and systematically incorporated as a potential tool in the application of the 'Gender Outcomes International Group: to Further Well-being Development' (GOING-FWD framework [13][14][15][16][17][18][19]. The GOING-FWD methodology has led to understand more clearly the effect of gender on outcomes also in population-based health surveys and in diverse clinical scenarios.…”
Section: What (And How) Gender-related Variables-gender Core Datasetmentioning
confidence: 99%
See 1 more Smart Citation